2012
DOI: 10.1038/mt.2012.165
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Mesenchymal Stem Cells Prevented Rejection of Allogeneic Corneal Transplants by Aborting the Early Inflammatory Response

Abstract: Mesenchymal stem/progenitor cells (MSCs) were reported to enhance the survival of cellular and organ transplants. However, their mode of action was not established. We here used a mouse model of corneal allotransplantation and demonstrated that peri-transplant intravenous (i.v.) infusion of human MSCs (hMSCs) decreased the early surgically induced inflammation and reduced the activation of antigen-presenting cells (APCs) in the cornea and draining lymph nodes (DLNs). Subsequently, immune rejection was decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 31 publications
(47 reference statements)
6
132
1
2
Order By: Relevance
“…injections of the cells at days −7 and −3. We carried out quantitative RT-PCR assays at day 0 for human-specific GAPDH as previously described (4,5), and detected less than 10 hMSCs in the tissues, an observation consistent with previous studies (4,5). Therefore, the beneficial effects of hMSC pretreatment in corneal allografts were not attributed to direct immunosuppression by hMSCs, and suggest induction of immune tolerance by hMSCs.…”
Section: Msc Pretreatment Improves Cornealsupporting
confidence: 83%
See 2 more Smart Citations
“…injections of the cells at days −7 and −3. We carried out quantitative RT-PCR assays at day 0 for human-specific GAPDH as previously described (4,5), and detected less than 10 hMSCs in the tissues, an observation consistent with previous studies (4,5). Therefore, the beneficial effects of hMSC pretreatment in corneal allografts were not attributed to direct immunosuppression by hMSCs, and suggest induction of immune tolerance by hMSCs.…”
Section: Msc Pretreatment Improves Cornealsupporting
confidence: 83%
“…Recently, observations by our group and others identified TSG-6 as being responsible for the beneficial effects of MSCs in the treatment of disease models of the heart (4), cornea (5,19,32), brain (33), lung (34), and pancreas (35). TSG-6 exerts its antiinflammatory actions through multiple mechanisms, one of which is the modulation of myeloid cells into a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to administer the MSCs before transplantation (day À7) as previous studies have shown enhanced efficacy when applied pretransplantation in preclinical models of cardiac (34) and kidney (35) transplantation. To date, a number of groups have investigated the ability of MSCs to repair chemically damaged corneas (20,(36)(37)(38) but relatively few have reported on the effects of MSCs on corneal allograft survival (22,39). To our knowledge, we show here for the first time that MSCs derived from a thirdparty strain are effective in prolonging corneal allograft survival.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, treatment of experimental corneal injuries in rabbits and limbal stem cell deficiencies in rats with MSCs has been reported (20,21); however, very little is known about the role of MSCs in the prevention of corneal allograft rejection. One recent study did report the therapeutic benefit of human MSC infusion in a fully allogeneic mouse model of cornea transplantation (22). The authors demonstrated that human MSCs can suppress the early surgery-induced inflammatory response leading to the prolongation of corneal allograft survival, an effect mediated, at least in part, by the increased production of tumor necrosis factor alpha (TNF-a) stimulated gene/protein 6.…”
Section: Introductionmentioning
confidence: 99%